Microsatellite (SSR) marker analysis to examine the effects of pesticide contamination on the genetic diversity of potato species - Rio, A. del; Bamberg, J.; Centeno Diaz, R.; Soto, J.; Salas, A.; Roca, W.; Tay, D. (Springer, 2011)
Many natural habitats concur in close proximity to cultivated fields and thus native plant species have an increased risk of indirect pesticide contamination. In recent years the USPG initiated an investigation to test the effects of agrichemicals on reproductive traits of diverse potato species. We found that the pesticide carbofuran is capable of reducing duration of flowering and pollen viability. These results suggested the possibility that negative changes in these traits could limit reproductive ability non-randomly and cause genetic drift. SSR markers were used to evaluate that possibility by assessing the genetic structure of progenies originated from potato populations exposed to two levels of carbofuran. Eight populations of 5 species (acl, buk, hcr, med and rap) were used in this study. An untreated, uncontaminated population was also included as control. The results revealed that most of the SSR frequencies assessed did not differ significantly between control and pesticide-contaminated progenies. However, a few SSRs showed significant frequency shift and it impacted genetic diversity levels in some species; specifically buk and med. Therefore, these studies reveal that pesticides near wild species populations not only reduce reproduction in general, but also may specifically change population genetics in a way that reduces diversity.